Corrective feedback in L2 Latvian classrooms: Teacher perceptions versus the observed actualities of practice. (July 2016) - Dilāns, Gatis
This two-part study aims to investigate teacher perceptions about providing oral corrective feedback (CF) to minority students of Latvian as a second language and compare the perceptions to the actual provision of CF in L2 Latvian classrooms. The survey sample represents sixty-six L2 Latvian teachers while the classroom observations involved 13 teachers of L2 Latvian from five minority schools in Latvia. The survey results show that all major types of oral CF were thought to be uniformly provided. The classroom observations, however, demonstrated a predominant provision of explicit, isolated recasts with the other types of feedback (explicit correction, elicitation, integrated recasts and repetition) present, yet trailing behind in terms of their use during classroom interactions.